2010
DOI: 10.1111/j.1471-4159.2010.07105.x
|View full text |Cite
|
Sign up to set email alerts
|

Insight into the mode of action of the LRRK2 Y1699C pathogenic mutant

Abstract: J. Neurochem. (2011) 116, 304–315. Abstract Mutations in the leucine‐rich repeat kinase 2 (LRRK2) gene are the most prevalent known cause of autosomal dominant Parkinson’s disease. The LRRK2 gene encodes a Roco protein featuring a Ras of complex proteins (ROC) GTPase and a kinase domain linked by the C‐terminal of ROC (COR) domain. Here, we explored the effects of the Y1699C pathogenic LRRK2 mutation in the COR domain on GTPase activity and interactions within the catalytic core of LRRK2. We observed a decreas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
136
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 118 publications
(140 citation statements)
references
References 47 publications
4
136
0
Order By: Relevance
“…In agreement with this model, PKA phosphorylation and subsequent binding of 14-3-3 might regulate LRRK2 kinase activity negatively by preventing dimerization of its ROC domain. Considering the recent findings by Daniëls et al (45), this negative regulation also might be mediated by 14-3-3, affecting the interaction of ROC with the adjacent COR domain. Future studies are needed to correlate PKA-mediated phosphorylation of pS1444 with 14-3-3 binding and LRRK2 activity in vivo.…”
Section: Discussionmentioning
confidence: 82%
“…In agreement with this model, PKA phosphorylation and subsequent binding of 14-3-3 might regulate LRRK2 kinase activity negatively by preventing dimerization of its ROC domain. Considering the recent findings by Daniëls et al (45), this negative regulation also might be mediated by 14-3-3, affecting the interaction of ROC with the adjacent COR domain. Future studies are needed to correlate PKA-mediated phosphorylation of pS1444 with 14-3-3 binding and LRRK2 activity in vivo.…”
Section: Discussionmentioning
confidence: 82%
“…The R1441 mutations cause a decrease in GTPase activity of LRRK2, although this activity is low and has been difficult to measure reliably, leading to some uncertainty about relevance of this observation [18][19][20]88]. The mechanism of diminished activity is likely via disruption of hydrogen bonding and stacking interactions normally provided by the arginine side chain [18][19][20]87], which may cause an enhancement in the affinity of LRRK2 for GTP with a subsequent decrease in GTP hydrolysis [89].…”
Section: Roc-cor Bidomain Mutationsmentioning
confidence: 99%
“…The Y1699 residue is located on the outer surface of the COR domain and substitution with cytosine at this likely alters interactions between the ROC and COR domains, leading to a reduction in GTPase activity [88,91]. As for R1441 mutations, the kinase function of Y1699C LRRK2 is similar to wild-type protein [13,44,67,68].…”
Section: Roc-cor Bidomain Mutationsmentioning
confidence: 99%
“…Recently, Daniëls et al reported the isolation of full length LRRK2 in solution from human embryonic kidney cells, however this protein is not widely available 13 . In contrast, the GST fusion truncated form of LRRK2 is commercially available (from Invitrogen, see table 1 for details), and provides a convenient tool for demonstrating an assay for LRRK2 kinase activity.…”
mentioning
confidence: 99%
“…Subsequently, purified recombinant fragments of LRRK2 in solution have also been used, for example a GST tagged fragment purified from insect cells containing residues 970 to 2527 of LRRK2 12 . Recently, Daniëls et al reported the isolation of full length LRRK2 in solution from human embryonic kidney cells, however this protein is not widely available 13 . In contrast, the GST fusion truncated form of LRRK2 is commercially available (from Invitrogen, see table 1 for details), and provides a convenient tool for demonstrating an assay for LRRK2 kinase activity.…”
mentioning
confidence: 99%